Stictodora cablei n. sp. (Digenea: Heterophyidae) from the royal tern, Sterna maxima (Laridae: Sterninae) from Puerto Rico and the Brazos County area of the Texas Gulf coast, U.S.A., with a list of other endohelminths recovered in Texas - Dronen, Norman O.; Blend, Charles K.; Gardner, Scott L.; Jiménez, F. Agustín (Zootaxa, 2007)
During a study of the endohelminths of wading birds from the Texas Gulf coast, 3 immature specimens of Stictodora (Heterophyidae) representing the same species that had previously been identified as Stictodora acanthotrema from the royal tern, Sterna maxima, in Puerto Rico by Raymond M. Cable, Robert S. Connor, and Jan W. Balling in 1960 were recovered from a royal tern, collected from the Bryan Utility Lake, Bryan, Texas. An additional 17 slides (14 whole mounts and 3 slides of sections) of this species that had been collected from this same bird host in Puerto Rico by Dr. Raymond M. Cable were examined from the holdings of the Harold W. Manter Laboratory of Parasitology, University of Nebraska, Lincoln, Nebraska. This species of Stictodora has the characteristic of the subgenus Galactosomoides and does not conform to the original description of Stictodora (=Acanthotrema) acanthotrema from the royal tern in Brazil, and it is therefore described as Stictodora cablei n. sp. The new species can be distinguished from all the other species in the genus by its unique acetabulogenital complex in which the acetabulum is highly modified with a small pad-like structure at its base surrounded by 3 papilliform arms extending sinistrally from it, whose outer edges fuse with the wall of the acetabulogenital sac, supporting the walls of the sac and the genital opening, and where the acetabulogenital sac contains a second, larger pad-like structure (the gonotyl described by Raymond M. Cable, Robert S. Conner, and Jan W. Balling in 1960) that extends from the left wall of the sac. Eleven other endohelminths were found in royal terns from Texas, U.S.A.: 3 cestodes, Angularella sp. (Dilepididae), an unknown genus and species of Dilepididae, and an unidentified immature cestode; 1 nematode, Contracaecum sp. (Anisakidae); and 7 trematodes, Cardiocephaloides brandesii (Strigeidae), Cercarioides cochleariformis (Heterophyidae), Mesostephanus fajardensis (Cyathocotylidae), Natterophthalmus andersoni (Philophthalmidae), Parorchis acanthus (Philophthalmidae), Stephanoprora conciliata (Echinostomatidae), and Stephanoprora denticulata (Echinostomatidae). Angularella sp., Contracaecum sp., M. fajardensis, S. conciliata, C. cochleariformis, and P. acanthus represent new host records. A checklist of parasites previously reported from the royal tern is also provided.